The Impact of the "One Million Plastic Caps" Project on Developing Environmental Awareness among Students at the Volunteer Summer Center in the Sultanate of Oman - Alhosni, Huda Ali; Alkahali, Amal Rabee; Alshkaili, Zahra Saif; AlSheyadi, Moza Ali (Journal of Educational and Psychological Sciences, 2025)
This study investigated the effectiveness of the One Million Plastic Caps project in promoting environmental awareness among students at the Volunteer Summer Center in the Sultanate of Oman. The study employed a quasi-experimental design with a single-group pre-test and post-test model to evaluate the effectiveness of the intervention. The sample comprised (17) students aged (9 to 14) years who participated in the Center’s programs. As part of the intervention, a comprehensive guide and training program were developed, and the Environmental Awareness Scale by Al-Sabbagh and Asab (2017) was administered both before and after the implementation. Results indicated statistically significant differences in favor of the post-test, reflecting improvement in students’ environmental awareness. In addition, participants demonstrated greater involvement in creative, hands-on activities and a marked decrease in screen time, replacing electronic device usage with environmentally themed artistic projects. This behavioral shift was associated with an enhanced sense of environmental responsibility. The study recommends expanding the initiative to schools and other summer programs to foster environmental awareness across a broader range of student populations. Furthermore, it advocates for the integration of recycling concepts into educational curricula, particularly through artistic and creative practices that support the development of environmental sustainability competencies.